Optimization of Customer Service with Respect to Profitability and Customer Satisfaction Case study of Hilti - Jindrák, Jiří (2013)
The Master's thesis focuses on customer satisfaction and its relationship to profitability, which is becoming an increasingly more relevant topic of daily discussion among the managers across all industries. The search for an optimal strategy that would lead to a consequent increase of both could be compared to a search for the "holy grail" or to an invention of the "perpetuum mobile" of business. The overall goal of my thesis is to design a strategy that would have the abovementioned attributes and would lead to an increase of profitability and customer satisfaction for the Hilti Czech republic and its after-market service. The theoretical part reviews the general academic literature connected with the topic. The practical part focuses on the company Hilti AG - a global premium provider of building construction tools and consumables in B2B segment, and examines especially its after-market service department. The first section of the practical part analyses the outcomes of the qualitative expert in-depth interviews with managers across different business units and departments and with real customers. The second part of the practical part proposes concrete steps that will lead to an increase of profitability and customer satisfaction.